2005
DOI: 10.1002/ijc.21063
|View full text |Cite
|
Sign up to set email alerts
|

Proteasome inhibitors can alter the signaling pathways and attenuate the P-glycoprotein-mediated multidrug resistance

Abstract: Numerous signaling pathways were reported to be involved in the resistance for conventional cytotoxic drugs, although one of the main reasons is the overexpression of P-glycoprotein (P-gp) in multidrug resistant cancer cells. The overexpression of P-gp has been associated with the resistance to a wide range of anticancer drugs. Doxorubicin and paclitaxel are substrates of this transporter system and have an important role for the various human malignancies. In the present study, drug-sensitive MCF7 and multidr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 40 publications
2
31
1
Order By: Relevance
“…12,13 In this study, the REIC/Dkk-3 overexpression in MCF7/ADR cells caused the c-Jun activation and P-glycoprotein downregulation in a JNK-dependent manner. Using the other adriamycinresistant cancer cell line, bladder cancer KK47/ADM, we also confirmed the overexpression of REIC/Dkk-3 because of Ad-REIC treatment to downregulate the P-glycoprotein expression in a JHK and c-Jun-dependent manner while also improving drug resistance (data not shown).…”
Section: Discussionmentioning
confidence: 63%
“…12,13 In this study, the REIC/Dkk-3 overexpression in MCF7/ADR cells caused the c-Jun activation and P-glycoprotein downregulation in a JNK-dependent manner. Using the other adriamycinresistant cancer cell line, bladder cancer KK47/ADM, we also confirmed the overexpression of REIC/Dkk-3 because of Ad-REIC treatment to downregulate the P-glycoprotein expression in a JHK and c-Jun-dependent manner while also improving drug resistance (data not shown).…”
Section: Discussionmentioning
confidence: 63%
“…Bortezomib and MG-132, proteasome inhibitors, reportedly reduced the degree of the MDR in MCF-7/DOX cells, 24) and MG-132 apparently reversed the MDR of gastric cancer by inhibiting P-gp. 25) These findings suggest that proteasome inhibitors attenuate the expression of P-gp and induce 27) In the RPMI-8226/TP-110 cells, our results clearly indicate that a proteasome inhibitor, TP-110, is the substrate of ABCB1 (P-gp).…”
Section: Discussionmentioning
confidence: 91%
“…Recent studies have shown that proteasome inhibition leads to an activation of the JNK pathway (16,52,80). As the JNK pathway is activated upon influenza virus infection and it is involved in antiviral signaling, whether PS-341 affects this signaling pathway in A549 cells has been investigated (44,45,48).…”
Section: Ps-341 Impairs Iav Propagation In a Variety Of Different Cellsmentioning
confidence: 99%